2014
DOI: 10.1371/journal.pone.0104279
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ATM/TP53/p21-Mediated Checkpoint Only Activated by Chronic γ-Irradiation

Abstract: Different levels or types of DNA damage activate distinct signaling pathways that elicit various cellular responses, including cell-cycle arrest, DNA repair, senescence, and apoptosis. Whereas a range of DNA-damage responses have been characterized, mechanisms underlying subsequent cell-fate decision remain elusive. Here we exposed cultured cells and mice to different doses and dose rates of γ-irradiation, which revealed cell-type-specific sensitivities to chronic, but not acute, γ-irradiation. Among tested ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…4A). Similar effects are observed in primary human fibroblasts cell lines during chronic exposure to IR [113]. Because lethal IR exposure irreversibly eliminates neoblasts, the results confirmed that key regulators of cell cycle progression and markers of proliferating neoblasts were nearly abolished upon IR (e.g.…”
Section: Evolutionarily Conserved Dna Damage Repair Mechanisms Exist supporting
confidence: 76%
See 1 more Smart Citation
“…4A). Similar effects are observed in primary human fibroblasts cell lines during chronic exposure to IR [113]. Because lethal IR exposure irreversibly eliminates neoblasts, the results confirmed that key regulators of cell cycle progression and markers of proliferating neoblasts were nearly abolished upon IR (e.g.…”
Section: Evolutionarily Conserved Dna Damage Repair Mechanisms Exist supporting
confidence: 76%
“…4C). ATM is an important player of the DDR that influences cellular decisions upon IR through reg- ulation of p53/p21 axis to facilitate cell cycle checkpoint arrest [113,118]. Thus, we can postulate that Smed-ATM may be key to facilitating an appropriate cellular response to DSBs (e.g.…”
Section: Evolutionarily Conserved Dna Damage Repair Mechanisms Exist mentioning
confidence: 99%
“…These features were primarily typical for the most affected group of IR-exposed patients, namely, cleanup workers engaged in action in the 2 nd quarter of 1986. These preliminary findings don't contradict the assumption on possible influence of IR on CLL development, and are in accordance with the data evidencing that cellular responses on IR are realized mainly through the p53-dependent pathway [28].…”
Section: Resultssupporting
confidence: 90%
“…5D, right model). By contrast, in normal cells with wild-type p53, the classical ATM-p53-p21 pathway is a dominant irradiation response pathway (25). The difference in our model was that the radiation dose was insufficient for stimulating overexpression and phosphorylation of p53.…”
Section: Discussionmentioning
confidence: 89%